Practical Issues of Medical Experts in Assessing Persons With Mental Illness Asking for Assisted Dying in Switzerland - Hachtel, Henning; Häring, Daniel; Kochuparackal, Tanya; Graf, Marc; Vogel, Tobias (Frontiers in Psychiatry, 2022)
With about 65,000 deaths per year in Switzerland, about 1,000 assisted suicides of Swiss citizens are carried out with the help of assisted dying organizations per year. Assisted suicide, which is carried out without selfish motives on the side of the helping person, only remains unpunished if there is a free will decision by the person willing to die who has the capacity of judgement and to act independently. While this is usually accepted as an option for somatically terminally ill patients in society at large, this procedure is controversial for psychiatrically ill patients. In Switzerland the topic of assisted dying is highly debated between medical professionals. In 2018, the Swiss Academy of Medical Sciences (SAMS) put revised guidelines into force, which are in discrepancy to the current rules of the Swiss Medical Association (FMH). This article gives an overview of the past and current development of the Code of Professional Conduct and medical-ethical guidelines as well as current Swiss criminal and medical law on this topic. Practical implications for the assessment of assessing persons with mental illness in this circumstances are discussed. It is to be concluded, that persons with a mental illness seem to face extra obstacles in relation with somatically ill persons as the assessment of the prerequisites comprises additional requirements. Among other issues there is an urgent need for the elaboration of contents to be assessed and standards of procedures. The procedures and guidelines to be elaborated should be scientifically accompanied in order to gain a more reliable basis for decision-making. Multidisciplinary assessments would help to avoid biases and blind spots of a mono-disciplinary assessments. In addition, even in the case of mentally ill people, their right to self-determined suicide should not be restricted by excessive hurdles in the assessment process. Lastly, reliable funding should be secured, as it is otherwise to be expected that the complex assessment of prerequisites through multi-professional-teams or just one assessor cannot be sustained. The exercise of fundamental rights must be possible for all persons to the same extent, regardless of their financial resources.